pH对玉米蛋白水解物功能特性的影响及其抗氧化活性分析Effect of pH on functional properties of corn protein hydrolysates and its antioxidant activity analysis - 李冠龙1,2，赵玉昊1,2，刘晓兰1,2，景言1，郑喜群2,3 LI Guanlong1,2, ZHAO Yuhao1,2, LIU Xiaolan1,2, JING Yan1, ZHENG Xiqun2,3 (Zhongguo youzhi)
为了促进玉米蛋白的开发利用，以玉米蛋白粉为原料，通过酶法制备玉米蛋白水解物（CPT），然后经超滤分级获得3个组分〔CPT1(分子质量>5 kDa)、CPT2(分子质量3~5 kDa)、CPT3(分子质量<3 kDa)〕，测定了各组分的粗蛋白质含量、谷氨酰胺含量和氨基酸组成，研究了pH对各组分功能特性的影响以及各组分的抗氧化活性。结果表明：玉米蛋白水解物各组分粗蛋白质含量范围为73.46% ~ 88.51%，超滤分级后大部分含有谷氨酰胺的肽段存在于较小分子质量的组分中；CPT3中总氨基酸含量最高，为71.83 g/100 g；在pH 2~9的范围内，CPT的溶解性最好,当pH为6时，CPT、CPT2、CPT3的溶解性最低，当pH为5时，CPT1的溶解性最低；在pH 5.0 ~ 7.0的范围内，CPT1在pH为7.0时有最大的乳化性和乳化稳定性，CPT2和CPT3在pH为6.2时有最大的泡沫稳定性，CPT3在pH为5.6时有最大的起泡性。与CPT相比，超滤分级后各组分的抗氧化活性有所提高，CPT、CPT1、CPT2和CPT3的羟自由基清除能力IC50分别为2.14、1.47、0.98 mg/mL和0.77 mg/mL（以蛋白质计），亚铁离子螯合能力IC50分别为2.05、1.01、1.33 mg/mL和1.16 mg/mL（以蛋白质计）。综上，pH对不同分子质量玉米蛋白水解物组分的功能特性的影响存在差异，其功能特性和分子质量分布有密切关系，今后可根据实际需求选择适合的组分应用于食品加工中。 In order to promote the development and utilization of corn protein, the corn protein hydrolysates (CPT) were prepared by enzymatic method with corn protein powder as raw material, and then three components, CPT1 (molecular weight > 5 kDa), CPT2 (molecular weight 3-5 kDa), and CPT3 (molecular weight < 3 kDa) were obtained by ultrafiltration grading. The contents of crude protein, glutamine, and amino acid compasition of each component were determined, and the effect of pH on the functional properties and antioxidant activity of each component were studied. The results showed that the crude protein content of each component ranged from 73.46% to 88.51%. Most of the glutamine-containing peptides after ultrafiltration grading were present in the smaller molecular weight fractions. CPT3 had the highest total amino acid content of 71.83 g/100 g. CPT had the best solubility in the range of pH 2-9. When the pH was 6, the solubility of CPT, CPT2 and CPT3 was the lowest, and when the pH was 5, the solubility of CPT1 was the lowest. In the range of pH 5.0-7.0, CPT1 had the maximum emulsification and emulsion stability at pH 7.0, CPT2 and CPT3 had the maximum foam stability at pH 6.2, and CPT3 had the maximum foaming property at pH 5.6. Compared with CPT, the antioxidant activity of each component after ultrafiltration grading was improved. The IC50 values of hydroxyl radical scavenging ability of CPT, CPT1, CPT2 and CPT3 were 2.14, 1.47, 0.98 mg/mL and 0.77 mg/mL (based on protein), and the IC50 values of ferrous ion chelating ability were 2.05, 1.01, 1.33 mg/mL and 1.16 mg/mL (based on protein), respectively. In conclusion, the effects of pH on the functional properties of different molecular weight corn protein hydrolysates components were different, and their functional properties were closely related to molecular weight distribution. In the future, suitable components can be selected for food processing according to actual needs.